2022
DOI: 10.32670/coopetition.v13i2.1423
|View full text |Cite
|
Sign up to set email alerts
|

Halal Awareness : Pengaruhnya Terhadap Keputusan Pembelian Konsumen Shopee dengan Religiositas Sebagai Variabel Moderasi

Abstract: Purpose- This study aims to determine and analyze the effect of the halal awareness variable on Indonesian Muslim consumers on purchasing decisions at Shopee with religiosity as a moderating variable. Design/Methodology/Approach – Using quantitative descriptive methods, this study analyzes responses to questionnaires distributed to 264 respondents from Indonesia. To prove this hypothesis, the data collected was analyzed by partial least squares (SEM-PLS) using SmartPLS. Findings – This research sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
5
0
3
Order By: Relevance
“…Regarding the concept of halal, consumer awareness of halal can influence consumer decisions to buy halal products. The existence of halal awareness to consume halal products is important for the community, especially Muslims (Juliana et al, 2022b). This is because products that have received halal certification are not only produced by Muslim producers but also produced by a number of non-Muslim groups (Zakaria et al, 2018).…”
Section: Concept Of Halal Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the concept of halal, consumer awareness of halal can influence consumer decisions to buy halal products. The existence of halal awareness to consume halal products is important for the community, especially Muslims (Juliana et al, 2022b). This is because products that have received halal certification are not only produced by Muslim producers but also produced by a number of non-Muslim groups (Zakaria et al, 2018).…”
Section: Concept Of Halal Awarenessmentioning
confidence: 99%
“…Halal awareness plays an important role in determining purchasing decisions. In indicators of purchasing decisions, halal awareness appears when consumers are aware of the importance of the concept of halal, so consumers will increasingly seek information about the product (Juliana, et al, 2022b). After that consumers will use the information to foster attitudes and actions in determining purchasing decisions.…”
Section: Concept Of Halal Awarenessmentioning
confidence: 99%
“…Hal tersebut sejalan dengan hasil riset dari Putri et al, (2019) Berdasarkan hasil uji hipotesis ke tujuh dimana terdapat pengaruh tidak langsung halal awareness terhadap keputusan pembelian melalui religiosity, dengan kata lain hipotesis diterima. Temuan tersebut konsisten dengan riset dari Juliana et al, (2022) terdapat pengaruh tidak langsung halal awareness terhadap keputusan pembelian melalui religiosity. Konsumen yang memiliki pengetahuan halal serta proses bagaimana halal itu harus dipenuhi oleh sebuah produk maka akan cenderung memiliki ketaatan menjalankan syariat agamanya.…”
Section: Pembahasanunclassified
“…The correlation between Muslims' comprehension of halal and their subsequent attitudes and actions towards halal-related matters is directly proportional. Juliana et al (2022) identified halal awareness indicators encompassing several dimensions. These dimensions include information pertaining to halal, the level of halal awareness, prioritization of purchasing halal products, adherence to product cleanliness standards, and assurance of product safety.…”
Section: Halal Awarenessmentioning
confidence: 99%